Obturator internus muscle strains - Caoimhe Byrne, MB BCh, BAO; Abdullah Alkhayat, BM BCh, FFRRCSI; Pat O'Neill, MB BCh, BAO, FFSEM(I), FFSEM (UK); Stephen Eustace, MB BCh, BAO, FFRRCSI; Eoin Kavanagh, MB BCh, BAO, FFRRCSI (Radiology Case Reports, 2017)
We report 2 cases of obturator internus muscle strains. The injuries occurred in young male athletes involved in kicking sports. Case 1 details an acute obturator internus muscle strain with associated adductor longus strain. Case 2 details an overuse injury of the bilateral obturator internus muscles. In each case, magnetic resonance imaging played a crucial role in accurate diagnosis.